2019
DOI: 10.12681/mms.18626
|View full text |Cite
|
Sign up to set email alerts
|

Updating the national checklist of marine fishes in Spanish waters: An approach to priority hotspots and lessons for conservation

Abstract: In response to a request from the Spanish Ministry of Farming, Fishing, Food, and Environment (Spanish: Agricultura, Pesca, Alimentación y Medio Ambiente) in 2015, a fish expert group was formed to provide a reference list of marine fish species according to five regions (marine demarcations) established by Spanish Law 41/2010 on the protection of the marine environment. The objective of this article was to update and analyse the data compiled in the marine fish species checklist in order to: 1) provide a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Hence, our results are not confounded by varying levels of fishing effort among groups of islands. It should be noted that, in this study, less than half of the batoids species known to occur in the Canary Islands (Báez et al, 2019; Brito et al, 2002; Appendix ) were recorded, even though our data covered a broad spectrum of sites, depths, and habitats. Estimating abundance patterns are crucial for any effective conservation initiative for batoids, including the establishment of protected areas for conservation at different geographic (e.g., insular) scales.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Hence, our results are not confounded by varying levels of fishing effort among groups of islands. It should be noted that, in this study, less than half of the batoids species known to occur in the Canary Islands (Báez et al, 2019; Brito et al, 2002; Appendix ) were recorded, even though our data covered a broad spectrum of sites, depths, and habitats. Estimating abundance patterns are crucial for any effective conservation initiative for batoids, including the establishment of protected areas for conservation at different geographic (e.g., insular) scales.…”
Section: Discussionmentioning
confidence: 65%
“…Despite the western islands being less populated than the central and eastern islands, SCUBA diving is of great popularity at the westernmost island (El Hierro), with nine diving centers and >20,000 divers per year, which, to a certain extent, rules out the potential low observation effort at the western islands (Meyers et al, 2017). In terms of the temporal frame of the data we here analyzed, it is worth mentioning that no publication from the study region has demonstrated a range shift for any batoid species (Báez et al, 2019). Despite a temporal comparison would be ideal to assess temporality in the presence of batoids in the Canary Islands, most UVC data (ca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By the end of 2020 there were 2.7 billion Facebook and 262 million Twitter users around the world (Garcia-Soto et al, 2021) and this increasing connection of people through social networks and web platforms such as Seawatchers.net is offering unprecedented opportunities to investigate marine biodiversity, especially in its most overlooked aspects. The distribution of Parapristipoma octolineatum (Valenciennes, 1833) (Haemulidae) comprehends the Eastern Atlantic, from Angola to the south of Spain and Portugal, including Cape Verde, Madeira, Canary Islands, and the Western Mediterranean; recently, in the Atlantic, it has been reported up to the Bay of Biscay and the Galician waters (Casamajor, 2016;Báez et al, 2019). For the Mediterranean basin, Bauchot (1987) reports the occurrence of the species along the coasts of Morocco and Algeria, in the Gibraltar Strait and the south and east coasts of Spain, while it is not listed among the Mediterranean ichthyofauna of eastern Spain in Báez et al (2019).…”
Section: New Records Of Uncommon Fish Species From the Western Mediterranean Sea: The Contribution Of Citizens Through The Seawatchersnetmentioning
confidence: 99%
“…The distribution of Parapristipoma octolineatum (Valenciennes, 1833) (Haemulidae) comprehends the Eastern Atlantic, from Angola to the south of Spain and Portugal, including Cape Verde, Madeira, Canary Islands, and the Western Mediterranean; recently, in the Atlantic, it has been reported up to the Bay of Biscay and the Galician waters (Casamajor, 2016;Báez et al, 2019). For the Mediterranean basin, Bauchot (1987) reports the occurrence of the species along the coasts of Morocco and Algeria, in the Gibraltar Strait and the south and east coasts of Spain, while it is not listed among the Mediterranean ichthyofauna of eastern Spain in Báez et al (2019). In Algeria, the species is considered extremely rare (Dieuzeide et al, 1955;Djabali et al, 1993).…”
Section: New Records Of Uncommon Fish Species From the Western Mediterranean Sea: The Contribution Of Citizens Through The Seawatchersnetmentioning
confidence: 99%